Analysing Early Childhood Educators' Science Pedagogy through the lens of a Pedagogical Content Knowing Framework. Issue 2 (June 2016) - Zhang, Weidong; Birdsall, Sally
CONCERNS HAVE BEEN RAISED about science education in early childhood settings. A revised model of pedagogical content knowledge consisting of four components of content and pedagogical knowledge, along with knowledge of learners and context, was used to analyse educators' science education pedagogy. Using an interpretive mode of inquiry with a case study approach, this study investigated the ways in which 20 New Zealand early childhood (EC) educators provided affordances for science learning in their centres. The findings revealed the educators used all four components, but asymmetrical use, together with little integration and synthesising of components, resulted in the potential of affordances for science learning offered not being realised. The pedagogical content knowing (PCKg) model proved valuable for identifying these educators' strengths and also areas for development. It was also argued that its use could provide a way for educators to reflect on their pedagogy, leading to the provision of transformed and more powerful knowledge.